Communications Experiences For Covid-19 Survivals Who Perform “Isolasi Mandiri” In Bandung - Kemalasari, Gyska; Hadisiwi, Purwanti; Prasanti, Ditha (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2022)
This study aims to find out: 1) Self-understanding of Covid-19 survivors; 2) Experience internal communication of Covid-19 survivors with family; 3) Experience external communication of Covid-19 survivors with environments outside the family. The method used in the research is qualitative method with phenomenological approach. The data collection technique in this study used in-depth interviews to five Covid-19 survivors who conducted self-isolation in Bandung. The theory used is the theory of symbolic interaction. The results of this study showed that the self-meaning of Covid-19 survivors who conducted self-isolation in this study was categorized as follows: a) fear; b) uncomfortable feeling and distrust others; c) feel sad to be temporarily separated from the family; d) feel bad for others; e) feel loved and cared for by others. Then the experience of internal communication of Covid-19 survivors with family, namely: a) maintaining physical distance and always using masks; b) communicate with electronic devices; c) communicate by shouting; d) communicate using the bell; e) given helpness in order to fulfill daily needs. As well as the experience of external communication of Covid-19 survivors with environments outside the family, namely: a) keeping a distance and tending to stay away physically; b) communicate with electronic devices; c) given helpness in order to meet the daily needs.